Three-dimensional structure of baculovirus-expressed Norwalk virus capsids. - Prasad, B V (1994)
The three-dimensional structure of the baculovirus-expressed Norwalk virus capsid has been determined to a resolution of 2.2 nm using electron cryomicroscopy and computer image processing techniques. The empty capsid, 38.0 nm in diameter, exhibits T = 3 icosahedral symmetry and is composed of 90 dimers of the capsid protein. The striking features of the capsid structure are arch-like capsomeres, at the local and strict 2-fold axes, formed by dimers of the capsid protein and large hollows at the icosahedral 5- and 3-fold axes. Despite its distinctive architecture, the Norwalk virus capsid has several similarities with the structures of T = 3 single-stranded RNA (ssRNA) viruses. The structure of the protein subunit appears to be modular with three distinct domains: the distal globular domain (P2) that appears bilobed, a central stem domain (P1), and a lower shell domain (S). The distal domains of the 2-fold related subunits interact with each other to form the top of the arch. The lower domains of the adjacent subunits associate tightly to form a continuous shell between the radii of 11.0 and 15.0 nm. No significant mass density is observed below the radius of 11.0 mm. It is suspected that the hinge peptide in the adjoining region between the central domain and the shell domain may facilitate the subunits adapting to various quasi-equivalent environments. Architectural similarities between the Norwalk virus capsid and the other ssRNA viruses have suggested a possible domain organization along the primary sequence of the Norwalk virus capsid protein. It is suggested that the N-terminal 250 residues constitute the lower shell domain (S) with an eight-strand beta-barrel structure and that the C-terminal residues beyond 250 constitute the protruding (P1+P2) domains. A lack of an N-terminal basic region and the ability of the Norwalk virus capsid protein to form empty T = 3 shells suggest that the assembly pathway and the RNA packing mechanisms may be different from those proposed for tomato bushy stunt virus and southern bean mosaic virus but similar to that in tymoviruses and comoviruses.